Hypogeous Ascomycetes of the western portion of the Transversal Volcanic System, Mexico - Gómez Reyes, Víctor Manuel; Vázquez Marrufo, Gerardo; Ortega Gómez, Alba María; Guevara Guerrero, Gonzalo (Instituto de Ecología, A.C., 2018)
Background and Aims: In Mexico, 42 species of ascomycetes have been reported with hypogeous habit, which are few considering the knowledge of other groups of fungi. The purpose of this paper is to increase the knowledge about the diversion and distribution of hypogeous fungi species for Mexico.Methods: Specimens were collected from different types of vegetation in the western portion of the transverse volcanic system, located in the state of Michoacán. The specimens collected were pictured and described following the protocols for the group.Key results: We present the description and discussion of six species of ascomycetes with hypogeous habit, Elaphomyces appalachiensis, Genea mexicana, Genabea cerebriformis, Hydnobolites cerebriformis, Tuber pseudoseparans and T. tequilanum.Conclusions: The records of these species represent new collection sites for Mexico and first records for the mycobiota of the state of Michoacán. It increases the distribution of Elaphomyces appalachiensis, Genabea cerebriformis and Hydnobolites cerebriformis, known from the United States of America and northern Mexico, to the Transversal Volcanic System, while Genea mexicana, Tuber pseudoseparans and T. tequilanum only are known in this mountainous system.